Probiotic supplementation causes hematological changes and improves non-specific immunity in Brycon amazonicus - Dias, Daniella de Carla; Tachibana, Leonardo; Iwashita, Marina Keiko Pieroni; Nakandakare, Ivan Bernardoni; Romagosa, Elizabeth; Seriani, Robson; Ranzani-Paiva, Maria José Tavares (Acta Scientiarum. Biological Sciences, 2020)
A commercial probiotic containing Bacillus subtilis (109 CFU g-1) was evaluated in caged matrinxã, Brycon amazonicus, by measuring hematological parameters and macrophage activity after 42 and 84 days after feeding. The product was added to commercial feed using 2% soybean oil as a protectant. A randomized three-treatment experiment was performed using four replicates per treatment. The groups included: (a) control without probiotic, (b) 5 g kg-1 probiotic, and (c) 10 g kg-1 probiotic. For hematological analysis, eight fish per treatment were used to determine total cell count (RBC); thrombocytes, differential, and total leukocyte count (TLC); hematocrit (Htc); hemoglobin tax; mean corpuscular volume (MCV); and mean corpuscular hemoglobin concentration (MCHC). Furthermore, plasma cortisol and glucose levels were measured in blood samples. Macrophage phagocytic activity was evaluated by injecting Saccharomyces cerevisiae (11,000 cells in a 3 mL volume) into the coelomic cavity incubating for 8 hours. Addition of probiotics to the diet of caged matrinxã altered the Htc, RBC, MCV, MCHC, TLC, lymphocyte, and eosinophil values. We observed increased cortisol and glucose levels and phagocytic activity, but no increase in the phagocytic index. We thus conclude that supplementing caged Brycon amazonicus with probiotics improves their non-specific immunity and alters blood profiles.